The Difference between Consistent and Inconsistent Planned Impulse Buying Based on External Stimulus and Virtual Cart Use - Ina Melati; Bernardinus M. Purwanto; Marwah Rizqiyati; Yulia Arisnani Widyaningsih; Bayu Sutikno (Bina Nusantara University, 2024)
Impulse-buying behavior is enjoyable for consumers and profitable for marketers. Selecting what they want and putting it in the shopping cart gives customers a sense of shopping enjoyment. However, the virtual shopping cart feature can be a barrier to impulse-buying behavior due to the abandonment of virtual carts. Sellers can overcome abandonment behavior in virtual carts by understanding consumer behavior, one of which is when exposed to external stimuli. The application of different external stimuli also produce different consumer behavior as well. The research aimed to validate the differences between Consistent Planned Impulse Buying (CPIB) and Inconsistent Planned Impulse Buying (IPIB) based on the influence of external stimuli: informativeness, appearance, and sales promotion, with the virtual cart used as the mediator variable using cognitive consistency theory. Data collection was carried out by distributing online questionnaires to 364 participants in Indonesia from October to November 2021 using a hierarchical linear model as the data analysis method. The analysis shows that sales promotion distinguishes between CPIB and IPIB. Sales promotions do not influence CPIB. Meanwhile, sales promotion affects IPIB. Hence, e-marketplace owners and their seller partners can apply the most appropriate external stimulus to induce impulse-buying behavior of different types. The research results also reveal a positive and significant relationship between the independent variables on virtual cart use and virtual cart on CPIB and IPIB.